Implementation of a competence approach in the context of modern Ukrainian secondary school as a basis of development of individual competences of senior pupils (Pedagogy of Higher and Secondary Education, 2013)
Pavlenko I. S. Implementation of a competence approach in the context of modern Ukrainian secondary school as a basis of development of individual competences of senior pupils.The main aspects of the competence-based approach realization under conditions of modern Ukrainian secondary school as the basis for the formation of high school students’ particular competences are highlighted in the article. The author elaborates on the meaning of the concepts of «competence» and «competency»that embody the competence approach, based on scientific potential of leading Ukrainian and foreign scientists.
Keywords: competence; competence-based approach; formation of competences; secondary school